Determination of Cu Environments in the Cyanobacterium Anabaena flos-aquae by X-Ray Absorption Spectroscopy - Kretschmer, X. C. (American Society for Microbiology (ASM), 2004)
Whole cells and peptidoglycan isolated from cell walls of the cyanobacterium Anabaena flos-aquae were lyophilized and used at pH 2 and pH 5 in Cu(II) binding studies. X-ray absorption spectra measured at the Cu K-edge were used to determine the oxidation states and chemical environments of Cu species in the whole-cell and peptidoglycan samples. In the whole-cell samples, most of the Cu retained at both pH values was coordinated by phosphate ligands. The whole-cell fractions contained significant concentrations of Cu(I) as well as Cu(II). An X-ray absorption near-edge spectrum analysis suggested that Cu(I) was coordinated by amine and thiol ligands. An analysis of the peptidoglycan fractions found that more Cu was adsorbed by the peptidoglycan fraction prepared at pH 5, due to increased chelation by amine and carboxyl ligands. The peptidoglycan fractions, also referred to as the cell wall fractions, contained little or no Cu(I). The Cu loading level was 30 times higher in the cell wall sample prepared at pH 5 than in the sample prepared at pH 2. Amine and bidentate carboxyl ligands had similar relative levels of importance in cell wall peptidoglycan samples prepared at both pH values, but phosphate coordination was insignificant.